Instrumen Tes Kebugaran Jasmani Untuk Anak Usia 10-12 Tahun - Bayu, Wahyu Indra; Waluyo, Waluyo; Victorian, Ahmad Richard; Al Ikhsan, Al Ikhsan; Apriyanto, Yoga (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The purpose of this study was to determine physical fitness measurement instruments for children aged 10-12 years. This is the average age of children who go to school at the primary level in grades 4-6. This type of research is a survey method with percentage descriptive data analysis techniques. Purposive accidental sampling was used in this study. Respondents involved in this study were 128 respondents consisting of 19 respondents who were lecturers in the field of sports and 109 respondents were teachers of PESH at elementary school. The results of the study show that the measuring instruments for health-related physical fitness that can be applied to most elementary schools by taking into account the condition of the facilities and infrastructure are weight, height, and body mass index (body composition), 20-meter multi-stage shuttle run (cardiorespiratory endurance), sit-and-reach test (flexibility), pushup (muscle endurance), and maximal handgrip strength test (muscle strength).